Is it all about the price? : reasons for the small market shares of organic meat and meat products in Austria - Wachter, Daniela (2016)
Austria is one of the leading countries in the world when it comes to organic farming. A closer look at the development of the market shares of different product categories reveals however, that some segments of organic products seemed to be constantly preferred while others were neglected by Austrian consumers over the past years: According to market statistics the categories “meat & poultry” and “ham & sausages” have the lowest market shares of organic fresh produce while at the same time, organic milk and organic eggs have the highest market shares. Since all of those organic products – milk, eggs as well as meat and meat products – are food of animal origin, for which the same organic criteria apply (the products are GMO free, the animals get no or less antibiotics and are bred in a species-appropriate way), one might wonder why the differences in the market shares are so big. The purpose of this thesis is therefore to figure out why Austrian consumers do not buy more organic meat and meat products. An additional task is to identify (realistic) measures to enlarge these small market shares. A review of existing studies on the consumption of organic products in general and organic meat and meat products in particular, an analysis of the Austrian organic market and the evaluation of interviews with several experts should provide answers to the research question. As most of the interviewed experts refer to the price as the only or at least one of several reasons for the small market shares of organic meat and meat products in Austria and this result confirms findings from the literature review and the analysis of the Austrian organic market, it seems that the difference in market share size is not all about the price, but mainly. The study provides further possible reasons as well as information on favourable and unfavourable conditions and measures for the growth of the small market shares and on the future development of (organic) meat consumption in Austria.